The Impact of Service Quality Relationship on Customer Loyalty at Legendary Restaurants R4 in Malang City - Riyadi, Sahrul Dwi; H.W., Agustina Shinta; Andriani, Dwi Retno; Anam, Moch Alawy Syaiful (HABITAT, 2024)
Each region certainly has its own culinary specialties, as Malang City is a tourist city that has many culinary specialties and has been established for a long time with hereditary recipes such as legendary restaurants R4. Culinary of a region is one of the main attractions for tourists, especially with the brand image that has been built in the general public which makes legendary culinary in Malang worth visiting. However, intense competition in the restaurant industry is also experienced by legendary restaurants in Malang, so efforts are needed so that legendary restaurants can continue to compete, one of which is by paying attention to the service quality provided to consumers so that consumers become loyal. In addition to aspects of service quality, legendary restaurants also need to pay attention to aspects of customer satisfaction, customer delight, and brand image which can later help build consumer loyalty and make legendary restaurants in Malang able to compete. Therefore, this research is very important to do to find out how far the effect of service quality on customer loyalty is through customer satisfaction, customer delight, and the role of brand image in moderating. This research was analyzed using SEM-PLS with 100 respondents with age criteria >17 years and having visited at least 2 times. This research shows that the service quality provided by the four restaurants has a positive and significant role on customer satisfaction, customer delight, and customer loyalty because the quality of service provided by the four restaurants is considered good, besides that brand image is able to strengthen the relationship between service quality and customer loyalty. So it is necessary for legendary restaurants to improve the quality of their services in order to get loyalty from their consumers and be able to compete with new restaurants.